2021
DOI: 10.1080/1750984x.2021.1931941
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Study

Abstract: Meta-study is a method for analysing the content and the process of knowledge production in a body of qualitative research. Conducting a meta-study involves four steps: (1) meta-dataanalysis which involves the study of empirical findings; (2) metamethod which examines the epistemological soundness and rigour of methods; (3) meta-theory which examines the structures, assumptions, and principles underpinning the primary research studies; and (4) meta-synthesis which brings the three steps together and considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(64 reference statements)
0
2
0
1
Order By: Relevance
“…Research using hashtags is a composite field of study, which required to adapt the classic meta-study procedures on it. To organize the salient elements that emerged from literature review, we can use some of the procedures identified there (Ronkainen et al, 2022). Thus, what emerged for the two lines of studies can be divided into the sub-branches of: theoretical perspectives and the social media (meta-theory); type of study (meta-method); analysis of results or conclusions (meta-data analysis) (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Research using hashtags is a composite field of study, which required to adapt the classic meta-study procedures on it. To organize the salient elements that emerged from literature review, we can use some of the procedures identified there (Ronkainen et al, 2022). Thus, what emerged for the two lines of studies can be divided into the sub-branches of: theoretical perspectives and the social media (meta-theory); type of study (meta-method); analysis of results or conclusions (meta-data analysis) (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…2.5.2. Analysis 2: Meta-Study Exploring Factors Signifying Opportunity for or Challenge to Healthy, Sustainable, and Equitable Mobility Systems We used the principles of meta-study [42] to describe and compare findings across studies in relation to the 'human urbanism' stage of the Human Mobility Transition (Table 2), using the prioritised exposures from the previous analysis stage. Meta-study involves four steps: meta-data analysis; meta-method; meta-theory; and meta-synthesis.…”
Section: Analysis 1: Charting and Prioritisingmentioning
confidence: 99%
“…Son olarak belirtilen üç bileşen meta-sentez sürecinde bir araya getirilir. Bu süreçte amaç, veri, yöntem ve teorinin analizinden türetilen bir fenomenin yeni bir yorumunu üretmektir (Ronkainen, Wiltshire ve Willis, 2022). Mevcut açıklamaların akla yatkınlığını, nelerin ihmal edildiğini ve bilginin ilerlemesi için hangi yeni yolların açıldığını dikkate alan meta-sentez süreci sonucunda meta-çalışma tamamlanmış olur.…”
Section: Meta-çalışma (Meta-study)unclassified